Analisis Penetapan Tarif Air Minum Berdasarkan Metode Full Cost Recovery Perumda Air Minum Tirta Bangun – Kulon Progo - Tatik; Eka Fariski, Resa (Relasi : Jurnal Ekonomi, 2024)
The determination of water tariffs is crucial for the sustainability of the Regional Water Company (Perumda). This sustainability, in turn, will impact the adequacy and service provision of drinking water for the community. This study aims to analyze the drinking water tariff using a qualitative approach. Perumda Water Company Tirta Binangun implements a full cost recovery policy to determine the value of the drinking water tariff. The calculation of the drinking water tariff by Perumda Water Company Tirta Binangun has followed the Regulation of the Ministry of Home Affairs of the Republic of Indonesia No. 71 of 2016 concerning the Calculation of Drinking Water Tariffs, but the percentage of drinking water loss at 23.45% still exceeds the regulation, which is set at 20%.